Quality changes in sea grape, Caulerpa lentillifera at different brine concentrations - Precious Dee H. Tolentino; Jerson C. Sorio (Journal of Fisheries, 2021)
Sea grapes are among the seaweeds being commercialized in the Philippines. They are sold in fresh state, and are highly perishable. It is necessary to develop preservation techniques in order to lengthen its shelf life. This study aims to assess the physico-chemical, microbial and sensorial quality of sea grape Caulerpa lentillifera preserved in 0%, 5%, 10% and 15% brine concentrations. Results revealed that brining effectively extended the shelf life of C. lentillifera by inhibiting the growth of bacteria and maintaining the osmotic pressure between the product and the solution. Within the 10 days storage period, 10% and 15% were bacteriologically stable and more acceptable upon rehydration. Treatments 0% and 5% were not acceptable because it exceeded the bacterial limit set for fresh vegetables. The sensorial attributes were compromised and became less acceptable due to degradation through bacterial action. In terms of physico-chemical analysis, high salt concentration (15%) decreased chlorophyll and carotenoid content significantly due to shrinkage and water loss. Overall, this study proved that sea grapes in 10% brine solution can extend its shelf life.